Patients’ and families’ experiences in Lung Tuberculosis treatment in Kebumen District, Central Java Province: A phenomenology study of ‘Drop Out’ and ‘Uninterrupted’ groups - Pratama Adi Prabawa; Mora Claramita; I Dewa Putu Pramantara (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
ABSTRACTBackground: Tuberculosis (TB) is still a worldwide health problem based on the impact of the disease, difficulties in the eradication and drop out tendency in treatment. One of the problems of TB in Indonesia is the high incidence of drop out treatment. Discontinuation of treatment leads to treatment failure, a source of transmission and drug resistance.Objectives: This study aimed to examine the process of meaning-making for the patients and their families’ as well as their PMO (Pengawas Minum Obat) / DOT-TB (Direct Obverser Treatment of Patients with Positive Pulmonary Tuberculosis) experience in pulmonary tuberculosis treatment of ‘Uninterrupted’ and ‘Drop Out’ groups.Methodology: A qualitative phenomenological approach was used with a purposive sampling strategy to select the participants. The data were collected by a psychologist with an in-depth interview with 7 patients and their families who continued the treatment until fully recovered (‘Uninterrupted’) and 7 patients and their families who dropped out the TB treatment (‘Drop out’) with the total subjects are 28 people. The location of research was in the Kebumen District which includes a Puskesmas (Community Health Center), Hospital and UP3 (Pulmonary Disease Treatment Unit). The Colaizzi method was used to analyze the data.Results: Patients' and their family's knowledge about TB of both groups were insufficient. However, the ‘Uninterrupted’ group were found to be self-motivated and received all possible psychological, and physical supports from their family while encouraging treatment adherence as factors that support the sustainability of pulmonary TB treatment. Whereas, these factors were not found in the ‘Drop out’ group.Conclusions: Self-motivation and family support / PMO for pulmonary TB patients is the key to the sustainability of pulmonary tuberculosis treatment until fully recovered. Education and counseling for pulmonary TB patients and their families / PMOs are absolutely necessary in Indonesia.